2023
DOI: 10.1002/wnan.1922
|View full text |Cite
|
Sign up to set email alerts
|

The future opportunities and remaining challenges in the application of nanoparticle‐mediated hyperthermia combined with chemo‐radiotherapy in cancer

Sakine Shirvalilou,
Zahed Tavangari,
Mohammad Hossein Parsaei
et al.

Abstract: A pivotal cause of death in the modern world, cancer is an insidious pathology that should be diagnosed at an early stage for successful treatment. Development of therapeutic interventions with minimal invasiveness and high efficacy that can discriminate between tumor and normal cells is of particular interest to the clinical science, as they can enhance patient survival. Nanoparticles are an invaluable asset that can be adopted for development of such diagnostic and therapeutic modalities, since they come in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…Laser interstitial hyperthermia therapy has shown great potential as a viable treatment option for patients who are prone to or currently experiencing wound complications resulting from previous treatments, based on various research studies. The cumulative evidence indicates that patients who have experienced previous wound complications or are at an elevated risk of impaired wound healing or wound dehiscence may avoid further worse complications by undergoing LITT 2,7,9,11,24–31 . Several studies have shown that patients undergoing LITT after experiencing previous complications have significantly fewer wound complications (1%–10%) than other treatment options 7,10,11,15–17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser interstitial hyperthermia therapy has shown great potential as a viable treatment option for patients who are prone to or currently experiencing wound complications resulting from previous treatments, based on various research studies. The cumulative evidence indicates that patients who have experienced previous wound complications or are at an elevated risk of impaired wound healing or wound dehiscence may avoid further worse complications by undergoing LITT 2,7,9,11,24–31 . Several studies have shown that patients undergoing LITT after experiencing previous complications have significantly fewer wound complications (1%–10%) than other treatment options 7,10,11,15–17 .…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative evidence indicates that patients who have experienced previous wound complications or are at an elevated risk of impaired wound healing or wound dehiscence may avoid further worse complications by undergoing LITT. 2 , 7 , 9 , 11 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Several studies have shown that patients undergoing LITT after experiencing previous complications have significantly fewer wound complications (1%–10%) than other treatment options. 7 , 10 , 11 , 15 , 16 , 17 While a few individuals reported only a few instances of wound complications following LITT, others stated that there were no reported occurrences of wound complications at all.…”
Section: Discussionmentioning
confidence: 99%
“… 27–30 Clinical evidence has consistently demonstrated that combining hyperthermia with chemotherapy effectively enhances local tumor control rates and prolongs patient survival. 31 Xia et al synthesized photo-responsive gold nanoparticles (AuNPs), which exhibited laser-induced accumulation towards the tumor and generated photothermal effects at the tumor site. 32 In vivo experiments conducted on 4T1 tumor-bearing mice demonstrated that laser-induced thermal effects significantly promoted local blood vessel expansion within the tumor area, thereby effectively enhancing the enrichment of chemotherapeutic drugs in the tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The next topic is combined thermo-and chemo-radiotherapy of cancer (Shirvalilou et al, 2023). At first, (magnetic) hyperthermia was used as a standalone treatment, but more recently it is applied to support more conventional treatments such as chemotherapy and radiation therapy.…”
mentioning
confidence: 99%